العلاقات الدبلوماسيّة وممارستها بين الحضارة الإسلاميّة والحضارة الغربية: دراسة مقارنة = The practice of diplomatic relationship between Islamic and Western civilization - Ibrahim, Nuri Faraj Salih; Mohammed Yaqub, Mohammed Abullais Shamsuddin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2018)
يُعَدُّ التمثيل الدبلوماسي من أشد الروابط التي تربط بين القبائل والدول والشعوب قديما وحديثا. وقد اهتم به فقهاء الإسلام وفقهاء غير المسلمين. ووضعوا له أنظمة وقوانين، ولكل من هؤلاء الفقهاء اتجاهات يتجهها في وضع نظريته للدبلوماسية. ومن ثم سبب اختلاف وجهات نظرهم في عملية ممارسة الدبلوماسية، وتحديد مسار عمل الممثل الدبلوماسي وما لها في الدولة المبعوث إليها وما عليها. وقد ساهم هذا البحث في بيان المفهوم الشامل للحصانة الدبلوماسية، وتاريخ نشأتها، وتطورها، مع كيفية ممارستها لدى الأمم والشعوب الغربية الماضية والحاضرة. ثم أعقب البحث بالمقارنة بذكر النظريات الغربية للحصانة الدبلوماسية، ومقارنتها بالنظام الإسلامي. ********************************************************** Diplomacy representation is one of the strongest links between tribes, states and peoples, in the ancient and modern. The Muslims’ jurists and non-Muslims' jurists were so much cared about it, and set rules and laws related to it. And each of these jurists has different trends in the development of diplomacy theory. And hence it leads to the difference of their views in the exercise of diplomacy, and determine the responsibilities of the diplomatic representative, his right, and what is not his right in the State and the mandate of the envoy. This research contributed to the comprehensive concept of diplomatic immunity, its history, its development and its practice in the past and present nations and peoples of the West. The research concludes with comparison between the Western and Islamic theories of diplomatic immunity.